Pengelolaan Dana BAntuan Operasional Sekolah (BOS) Di SD N Kemasan I Surakarta - Widyatmoko, Subkhi, Dr.Suyatmini,SE.,M.Si, Dr.Wafrotur Rohmah, M.M (2017)
This study aims to describe (1) Planning of school operational funds (BOS) (2) the implementation of of school operational funds (BOS) (3) accountability of school operational funds (BOS) on Elementary School of Kemasan I Surakarta. This study used a qualitative research with a ethnographic approach. The technique of collecting data through interviews, observation and documentation.The method of data analysis the technique of done by using several stages of data collection, data reduction, data presentation, and data verification. The testing of data validity is done by using triangulation techniques sources and methods. The results of the study concluded (1) in the planning process components involved, among others, the principal in charge, the school treasurer, board of teachers and school committee. The planning process begins with preparing RAKS by Bos management team, teachers and the School Committee. (2) The implementation of BOS management begins with withdrawals made treasurer as required by leaving a minimum balance in the bank. Withdrawal is done quarterly. The money has been taken from the Bank cash deposited in the school by the treasurer. Expenditures that did not make the 13 items in the governance of the BOS funds using dues charity students held every Friday. (3) Accountability BOS conducted by the school treasurer, worked every day the report done gradually in accordance with the planned budget in the preparation of sport teachers in reporting, there are two methods of offline and online. In the BOS management there are some books that should be made in the governance of the BOS is a common cash book, General Ledger Cash, Bank Ledger, Ledger Tax. Keywords: management, school operational funds (BOS), Elementary School